Dexamethasone changes the pharmacokinetics of amitriptyline and reduces its accumulation in rat brain: The roles of P-gp and cyp3a2 - Jing Wen; Yuan Shen; Min Zhang; Chao Wang; Yalan Xiang; Hualin Cai; Pingfei Fang; Huande Li (Elsevier, 2019)
The wide spread use of central nervous system (CNS) drugs has caused thousands of deaths in clinical practice while there are few antidotes or effective treatments to decrease their accumulation in CNS. In this study, we used amitriptyline (AMI) and dexamethasone (DEX) as the corresponding poisoning and pre-protecting drugs, respectively, to study whether DEX has the potential to reduce AMI accumulation in brain. By measuring the pharmacokinetic data of AMI and its main metabolite nortriptyline (NOR), we found that DEX possibly accelerated the metabolism and elimination of AMI with minimal effects on the concentrations of NOR in blood. Nevertheless, the results indicated that DEX reduced the brain/plasma concentration ratio of AMI and NOR, even if the plasma concentration of NOR had an upward trend. Western blot results showed the overexpression of cyp3a2 and P-gp in rat liver and brain capillaries tissues. We propose that cyp3a2 and P-gp could be upregulated in the liver and blood-brain barrier (BBB) when using DEX. Further experiments suggest that DEX may serve as the ligand of PXR to induce P-gp expression. Keywords: Amitriptyline, Dexamethasone, Pharmacokinetics, Blood-brain barrier, P-gp